PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PENYULUH TERHADAP KOMPETENSI PENYULUH DI NUSA TENGGARA TIMUR - Jelamu Ardu Marius; Sumardjo Sumardjo; Margono Slamet; Pang S. Asngari (Jurnal Penyuluhan, 2007)
The objectives of this research were to portray the influence of internal and external factors to the competencies of the agricultural extension agents. The individual characrterization of the agricultural extension agents were the internal factors which assumed to influence in creating the competencies, and those other i.e the non formal education (diklat), the milieu, and the extension organization structure were the external factors. The respondents were selected by the random and purposive sampling method in the three regency as research area. Data analysis was done by using descriptive and Linear Structural Relationship (LISREL) program 8.72 by Structural Equation Modelling (SEM) models. The results of the research showed that the internal factors were influenced positively and significantly to the competencies of the agricultural extension agents both before and after the autonomy, but those other were not.